If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6x + x + -9x = 0 Combine like terms: 4x + -6x = -2x -2x + x + -9x = 0 Combine like terms: -2x + x = -1x -1x + -9x = 0 Combine like terms: -1x + -9x = -10x -10x = 0 Solving -10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-10'. x = 0.0 Simplifying x = 0.0
| -2a+-9=6a+13 | | 3x-7+9-2x=x+1 | | -2a-9=6a+143 | | -42-6x=x+70 | | 4x-5x+2x-6x= | | -6x-18=8-7x | | 4x+13+15x+15=180 | | 2.5-0.02x=1.08 | | -3+46=8x+4-5x | | 2+-4y=10 | | 5x-17=9+7x | | 4a=4a+6 | | 45-[5+7y-2(y+4)]=-5(4y-3)-[9(y-1)-16y+8] | | 3/4g+2.5=4/3g-2.4 | | 3x^2-8+20=0 | | 7.5=9.1-0.8x | | 2x-52=109+9x | | -8n+2(n+4)= | | 6(n+8)=36 | | 7(q+2)-19= | | 8b-2a= | | 2x+5x-5=16 | | 3(x+35)=8 | | 2y=24x+0.4 | | .7(3-x)=8(4-2x) | | 10w-15w=30 | | -n+5=-6 | | 3+6=x-4 | | -5(-5+n)+3n= | | 2(x-14)+34=x+3x+3(x+4) | | 7x+13=8x+2 | | 3(3x-1)=-2(X+3) |